2017
DOI: 10.3892/ol.2017.6999
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and XIAP expression in distinct tumor compartments of surgically resected gastric cancer: XIAP as a prognostic marker in diffuse and mixed type adenocarcinomas

Abstract: Abstract. There is considerable evidence that the inhibitor of apoptosis protein (IAP) family serves a role in tumorigenesis. The most studied IAP family members, survivin and X-linked inhibitor of apoptosis (XIAP), have been demonstrated to serve as biomarkers in distinct tumor entities. Thus, the present study aimed to investigate the expression levels of both IAPs in the tumor center, invasion front and lymph node metastases of surgically resected gastric cancer (GC) specimens. Tissue microarrays containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…All studies were retrospective design and the sample size ranged from 29 to 1103. The patients were diagnosed with various solid carcinomas, among which digestive tumors accounted for the most type, particularly gastric cancer (n=4) 25-28, colorectal cancer (n=3) 29-31, HCC (n=5) 12, 17, 32-34, esophageal cancer (n=2) 11, 35, cholangiocarcinoma (n=2) 36, 37 and pancreatic cancer (n=1) 38. And the remaining studies included breast cancer (n=4) 16, 18, 19, 39, NSCLC (n=2) 13, 40, head and neck cancer (HNC) (n=4) 41-44, thyroid cancer (n=4) 15, 45-47, prostate cancer (n=2) 14, 48, renal cancer (n=2) 49, 50 and other tumor types (n=5) listing as: sebaceous gland carcinoma, glioblastomas, ovarian cancer, bladder cancer and malignant mesothelioma 51-55.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were retrospective design and the sample size ranged from 29 to 1103. The patients were diagnosed with various solid carcinomas, among which digestive tumors accounted for the most type, particularly gastric cancer (n=4) 25-28, colorectal cancer (n=3) 29-31, HCC (n=5) 12, 17, 32-34, esophageal cancer (n=2) 11, 35, cholangiocarcinoma (n=2) 36, 37 and pancreatic cancer (n=1) 38. And the remaining studies included breast cancer (n=4) 16, 18, 19, 39, NSCLC (n=2) 13, 40, head and neck cancer (HNC) (n=4) 41-44, thyroid cancer (n=4) 15, 45-47, prostate cancer (n=2) 14, 48, renal cancer (n=2) 49, 50 and other tumor types (n=5) listing as: sebaceous gland carcinoma, glioblastomas, ovarian cancer, bladder cancer and malignant mesothelioma 51-55.…”
Section: Resultsmentioning
confidence: 99%
“…The rest studies were further evaluated in full text and 31 were excluded due to unrelated, lacking enough data or other reasons. Eventually, 12 studies [ 12 , 14 22 , 24 , 25 ] met the inclusion criteria and were included. The study selection process was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may suggest different roles of XIAP in squamous cell carcinoma and adenocarcinoma. Dizdar et al [ 22 ] also investigated the prognostic role of XIAP in gastric cancer. Although the pooled HR from multivariate analysis was not significant in all subtypes of gastric cancer, they found that XIAP could be an independent prognostic marker in both diffuse type and mixed type of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, XIAP and survivin are members of the inhibitor of apoptosis (IAP) protein family that inhibit caspases and block cell death. These proteins are highly expressed in most types of cancer cell and are associated with a poor clinical cancer treatment outcome [19]. The overexpression of these four proteins in cancer cells may block or delay the onset of apoptosis by selecting and maintaining the long-living cancer cells in the G0 phase of the cell cycle.…”
Section: Anti-cancermentioning
confidence: 99%